Acute colic secondary to sand enteropathy (sablosis) in a horse - Althea Wang; Chi Hin Ng; Viviana Gonzalez Astudillo (Brazilian Journal of Veterinary Pathology, 2025)
History: A 24–year-old Stockhorse gelding presented for veterinary assessment after developing profuse watery diarrhea. The horse presented with a distended abdomen, decreased gut sounds on both quadrants on the left-hand side, absent gut sounds on the right-hand side and was hypothermic (36.8°C) with a heart rate of 44 bpm. The horse was drenched with water, paraffin oil and electrolytes via a nasogastric tube. No net reflux was obtained. Despite the administration of pain relief and sedation, the gelding’s heart rate continued to increase to 68 bpm. The gelding was transported to a referral service but died upon arrival.